Remote control ebook - Okorafor, Nnedi (2021)
An alien artifact turns a young girl into Death's adopted daughter in Remote Control , a thrilling sci-fi tale of community and female empowerment from Nebula and Hugo Award-winner Nnedi Okorafor "She's the adopted daughter of the Angel of Death. Beware of her. Mind her. Death guards her like one of its own." The day Fatima forgot her name, Death paid a visit. From hereon in she would be known as Sankofa—a name that meant nothing to anyone but her, the only tie to her family and her past. Her touch is death, and with a glance a town can fall. And she walks—alone, except for her fox companion—searching for the object that came from the sky and gave itself to her when the meteors fell and when she was yet unchanged; searching for answers. But is there a greater purpose for Sankofa, now that Death is her constant companion? Winner of the AudioFile Earphones Award (audiobook version). At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.